Experimental investigation on the reverse mechano-electrical effect of porcine articular cartilage - Chunsheng Liu; Le Zhao; Hao Dong; Zekun Hua; Yanqin Wang; Yongxing Wang; Pengcui Li; Xiaochun Wei; Kai Zhang; Yanru Xue; Xiaogang Wu; Weiyi Chen (Frontiers in Bioengineering and Biotechnology)
IntroductionThe electric signals within the cartilage tissue are essential to biological systems and play a significant role in cartilage regeneration. Therefore, this study analyzed and investigated the reverse mechano-electrical effect in porcine articular cartilage and its related influencing factors.MethodsThe deflection of cartilage samples in an electric field was measured to analyze the mechanisms of different factors affecting the reverse mechano-electrical effect in articular cartilage.ResultsThe results showed that the cartilage thickness, water content, and externally applied voltage all impacted the deflection of the cartilage. The reduction in cartilage water content resulted in a decrease in cartilage thickness, following the same influencing mechanism as thickness. On the other hand, an increase in the externally applied voltage led to an increase in the electric field force within the cartilage space, consequently increasing the deflection of the cartilage in the electric field. Additionally, the externally applied voltage also caused a slight temperature rise in the vicinity of the cartilage specimens, and the magnitude of the temperature increase was proportional to the externally applied voltage.DiscussionThe fitting results of the experimental data indicated that cartilage thickness influenced the dielectric constant and moment of inertia of the cartilage in the electric field, thereby affecting the magnitude of the electric field force and deflection of the cartilage. This may provide valuable insights for further investigation into the microscopic mechanisms of cell proliferation, differentiation, and cartilage regeneration induced by electrical stimulation.